2018
DOI: 10.1051/meca/2016083
|View full text |Cite
|
Sign up to set email alerts
|

Impact of brass contents on thermal, friction and wear properties of brake linings composites

Abstract: Automotive brake lining materials are composite materials of very complex formulation, highly heterogeneous. They help to carry out the desired combination of braking performance properties. Obviously, it requires that the friction material exhibits good complementarities and adequate combination of physico-chemical, thermal properties that act synergistically to provide the braking performance which should be adjusted by the addition of metallic fillers. The aim of this work is to study the role of one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Further, the particle morphology helps the resin to bond more iron powder, which improves the strength and enhances the tribological performance, and this can be substituted in the place of steel fiber. Sellami et al 7 studied brake pads made with 1.5, 3, and 4.5 wt.% of brass and observed that increase of brass contents increased the thermal conductivity and diffusivity in a positive way. Also, he concluded that brake pad with 4.5% of brake pad resulted in good fade resistance and wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the particle morphology helps the resin to bond more iron powder, which improves the strength and enhances the tribological performance, and this can be substituted in the place of steel fiber. Sellami et al 7 studied brake pads made with 1.5, 3, and 4.5 wt.% of brass and observed that increase of brass contents increased the thermal conductivity and diffusivity in a positive way. Also, he concluded that brake pad with 4.5% of brake pad resulted in good fade resistance and wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Further increase in zinc above 2 % improves wear resistance by reducing the fade performance of the brake which is essential. The effect of brass (an alloy of copper and zinc) powder content on the tribological performance of NAO brake composite was evaluated by Sellami et al [12] and found that the addition of inferred that the samples with 4.5 % created plateaus and conversely if added less than 4.5% brass improved the wear performance. They also removed the material from the matrix implying a higher source of third body wear.…”
Section: Introductionmentioning
confidence: 99%
“…That is because similarly to copper, brass improves thermal conductivity [191,193]. Thus, more intense penetration of heat into the material takes place, which in turn accelerates the degradation of the matrix [192,194]. Moreover, brass demonstrates lubricating properties.…”
Section: Abrasivesmentioning
confidence: 99%